Light‐Boosting Highly Sensitive Pressure Sensors Based on Bioinspired Multiscale Surface Structures. (19th February 2020) - Yu, Shixiong; Li, Lele; Wang, Juanjuan; Liu, Enping; Zhao, Jingxin; Xu, Fan; Cao, Yanping; Lu, Conghua
Abstract: Pressure sensors have attracted tremendous attention because of their potential applications in the fields of health monitoring, human–machine interfaces, artificial intelligence, and so on. Improving pressure‐sensing performances, especially the sensitivity and the detection limit, is of great importance to expand the related applications, however it is still an enormous challenge so far. Herein, highly sensitive piezoresistive pressure sensors are reported with novel light‐boosting sensing performances. Rose petal–templated positive multiscale millimeter/micro/nanostructures combined with surface wrinkling nanopatterns endow the assembled pressure sensors with outstanding pressure sensing performance, e.g. an ultrahigh sensitivity (70 KPa −1, <0.5 KPa), an ultralow detection limit (0.88 Pa), a wide pressure detect ion range (from 0.88 Pa to 32 KPa), and a fast response time (30 ms). Remarkably, simple light illumination further enhances the sensitivity to 120 KPa −1 (<0.5 KPa) and lowers the detection limit to 0.41 Pa. Furthermore, the flexible light illumination offers unprecedented capabilities to spatiotemporally control any target in multiplexed pressure sensors for optically enhanced/tailorable sensing performances. This light‐control strategy coupled with the introduction of bioinspired multiscale structures is expected to help design next generation advanced wearable electronic devices for unprecedented smart applications. Abstract : Highly sensitive piezoresistive pressure sensors are fabricated on the base of bioinspired (i.e., biotemplating and surface wrinkling) multiscale structures. Remarkably, light illumination further enhances the sensitivity and lowers the detection limit. The flexible light control offers great capabilities to spatiotemporally manipulate any target in multiplexed pressure sensors for on‐demand sensing performance and unprecedented smart applications.